An illustrated treasury of myths and legends - Riordan, James 1936-2012; Lewis, Brenda Ralph; Ambrus, Victor G. (London Dean, part of Reed International Books Limited, 1991)
An international collection of twenty-five tales of courage, daring, and romance, featuring heroes such as Robin Hood, El Cid, Perseus, and Volund.
Originally published: London : Hamlyn, 1987
Keywords: Tales; Mythology -- Juvenile literature; Legends